1995
DOI: 10.2190/mhur-4fc9-b187-t8h4
|View full text |Cite
|
Sign up to set email alerts
|

Computer use by School-Age Children: Trends, Patterns, and Predictors

Abstract: Patterns of computer use are studied based on analysis of data from the Longitudinal Study of American Youth (LSAY) in which a cohort of students and their parents were surveyed for five consecutive years. Special attention is given to students who were heavier users of computers. Heavier use is associated with high SES as well as superiority in grades. Heavier use declined as this cohort progressed from the seventh grade to high school despite increasing access to computers at home. Parents with computers at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 7 publications
3
44
0
1
Order By: Relevance
“…Ho and Lee (2001) found that male computer users who spent more time on computer-mediated communication, surfing the Internet and doing homework tended to have greater perceived social support. Rocheleau (1995) also reported that heavier computer users were similar to other students in social activities. Research relating to computer users who primarily play games has elicited mixed results.…”
Section: Social Developmentmentioning
confidence: 86%
See 1 more Smart Citation
“…Ho and Lee (2001) found that male computer users who spent more time on computer-mediated communication, surfing the Internet and doing homework tended to have greater perceived social support. Rocheleau (1995) also reported that heavier computer users were similar to other students in social activities. Research relating to computer users who primarily play games has elicited mixed results.…”
Section: Social Developmentmentioning
confidence: 86%
“…Whilst the evidence is mixed, it does appear that computers can enhance academic performance. Home computer ownership has been shown to be positively related to performance on standardised academic tests (Rocheleau 1995, Attewell and Battle 1999, Harrison et al 2002, Attewell et al 2003, Borzekowski and Robinson 2005. Effect sizes vary, with Harrison et al (2002) and Attewell et al (2003) describing modest but positive effects, while Borzekowski and Robinson (2005) report a more substantial effect.…”
Section: Cognitive Developmentmentioning
confidence: 99%
“…Comber et al (1997) found that in the older age group in their research, the boys used the computer at school more than the girls but that such a difference did not exist in the younger students (aged 11 and 12). A long-term study in the United States (Rocheleau, 1995) showed that the initial significant difference in computer use by girls and boys in the highest classes of primary education gradually diminished until it was no longer significant in 1992. Neither Doornekamp (1993) nor Durndell and Thomson (1997) found gender differences in the use of computers at school.…”
Section: Accessmentioning
confidence: 99%
“…Recent studies of how people learn to use computers from the social developmental perspective concern various issues. These issues can be grouped into the following categories: (1) Internet addiction (Davis, Smith, Rodrigue, and Pulvers, 1999;Griffiths, 1997;Young, 1996), (2) social identity and personality (Turkle, 1984(Turkle, , 1995Ike, 1997), gender difference and stereotype (Rocheleau, 1995;Schott and Selwyn, 2000), (3) computer anxiety and phobia , (4) social interaction and socialization (Crook, 1992;Freeman and Somerindyke, 2001;Lawhorn, Ennis, and Lawhorn, 1996;McKenna, 1999), and (5) life intrusion, privacy, and on-line predators (U. S.…”
Section: Human Development and Learning To Use Computersmentioning
confidence: 99%